(untitled) (International Journal of Engineering and Computer Science, 2015)
Downloading any file quickly is a part of our social as well as professional living. The modern society can not work without various downloading facilities. There are many systems which are providing quick downloading of large files for personal and corporate world. If the server has 1GB data with the 100Mb/S transfer speed then theoretically it will take 10 to 20 seconds to transfer data to client PC. But it actually takes 60 to 90 seconds. It gives only 10% to 20% of actual throughput. Proposed system will provide facility for downloading file within minimum time with help of Network Coding. So that the client who will download the file for very first time, he will download it from server. When the other user will try to download it then the first downloaded image will work as replica for the current downloading. This system will use parallel file downloading protocols. The server will keep record of files present on every client in a tabular format. The concept of Distributed Storage can also be implemented. Hence the proposed system will increase the throughput upto 30% to 40%.